Arabidopsis TCP Transcription Factors Interact with the SUMO Conjugating Machinery in Nuclear Foci - Mazur, Magdalena J.; Spears, Benjamin J.; Djajasaputra, André; van der Gragt, Michelle; Vlachakis, Georgios; Beerens, Bas; Gassmann, Walter; van den Burg, Harrold A. (Frontiers in Plant Science, 2017)
In Arabidopsis more than 400 proteins have been identified as SUMO targets, both in vivo and in vitro. Among others, transcription factors (TFs) are common targets for SUMO conjugation. Here we aimed to exhaustively screen for TFs that interact with the SUMO machinery using an arrayed yeast two-hybrid library containing more than 1,100 TFs. We identified 76 interactors that foremost interact with the SUMO conjugation enzyme SCE1 and/or the SUMO E3 ligase SIZ1. These interactors belong to various TF families, which control a wide range of processes in plant development and stress signaling. Amongst these interactors, the TCP family was overrepresented with several TCPs interacting with different proteins of the SUMO conjugation cycle. For a subset of these TCPs we confirmed that the catalytic site of SCE1 is essential for this interaction. In agreement, TCP1, TCP3, TCP8, TCP14 and TCP15 were readily SUMO modified in an E. coli sumoylation assay. Strikingly, these TCP-SCE1 interactions were found to redistribute these TCPs into nuclear foci/speckles, suggesting that these TCP foci represent sites for SUMO (conjugation) activity.